Improving electron trans-inner membrane movements in microbial electrocatalysts. Issue 37 (18th April 2016) - Tao, Le; Xie, Mingshi; Chiew, Geraldine Giap Ying; Wang, Zhijuan; Chen, Wei Ning; Wang, Xin
Abstract : A microbial fuel cell loaded with engineered bioelectrocatalysts shows significantly enhanced performance by promoting the utilization of intracellular primary electron donors in bioelectrocatalysts. Abstract : A novel nondestructive strategy of improving electron trans -inner membrane movements in bioelectrocatalysts is realized by overexpressing NADH dehydrogenase II in the inner membrane. A microbial fuel cell loaded with these improved bioelectrocatalysts shows significantly enhanced performance based on promoting the utilization of intracellular primary electron donors in bioelectrocatalysts.